New find of Dactylophrya-stage of parasitic suctorian of genus Tachyblaston Martin, 1909 (Ciliophora, Suctorea) with comments on genus taxonomy - Chatterjee, Tapas; Dovgal, Igor; Sautya, Sabyasachi (Zootaxa, 2023)
The article presents the new find of Dactylophrya-stage of rare parasitic suctorian ciliate of genus Tachyblaston on harpacticoid copepod from Mumbai, India. The found specimen was identified as Tachyblaston reversum (Collin, 1909), n. comb. The redescription of T. reversum was provided. The refined diagnoses of genus Tachyblaston and included species, data on distribution of genus representatives, synonymy and comments on genus taxonomy are also presented.